Perlindungan Hukum Bagi Dokter Umum Terkait Pelimpahan Wewenang Tindakan Medik dari Dokter Spesialis Menurut Omnibus Law Kesehatan 2023 - Jaury Douglas Pardomuan; Handoyo Prasetyo (Lembaga Pengembangan Kinerja Dosen, 2024)
In carrying out their duties, general practitioners have limitations both in terms of knowledge and medical facilities they possess. Furthermore, based on the Omnibus Health Law 2023, there are regulations that govern general practitioners regarding the medical procedures they can and cannot perform. Several articles that regulate referral issues are Article 19, Article 32, Article 189, and Article 360. Meanwhile, the regulation regarding specialist doctors is listed in Articles 233-235. However, it is important to emphasize that the authority of specialist doctors and general practitioners is not directly regulated in the Omnibus Law. Thus, the study that can be conducted is an interpretative study that compares it simultaneously with similar legal products. Other references that can be used are Presidential Regulation no. 31 of 2019 and Minister of Health Regulation no. 36 of 2019. Based on a comparative study and judicial analysis of the Omnibus Health Law 2023, specialist doctors have their own independence, and therefore, if they delegate authority to general practitioners, it is guaranteed by the law, including the Omnibus Health Law 2023, especially because the Omnibus Health Law 2023 opens up flexibility for specialist doctors to practice. If delegation occurs, general practitioners can be legally protected as long as the basis for this delegation is emergency for patient safety, secondly is the delegation of authority to ensure patient safety, and thirdly is part of the education for specialist doctors. Although not explicitly stated, these implications are strongly implied in the articles mentioned in the Omnibus Health Law. Nevertheless, there are certain limits that specialist doctors must follow to ensure that patients' rights are well protected, and in the future, there needs to be a strengthening of regulations so that both general practitioners and specialist doctors do not face criminalization.